DSS-induced colitis activates the kynurenine pathway in serum and brain by affecting IDO-1 and gut microbiota - Zhao, Li-Ping; Wu, Jian; Quan, Wei; Zhou, Yu; Hong, Hui; Niu, Gu-Yu; Li, Ting; Huang, Shu-Bing; Qiao, Chen-Meng; Zhao, Wei-Jiang; Cui, Chun; Shen, Yan-Qin (Frontiers in Immunology, 2023)
Increasing studies have found that inflammatory bowel disease (IBD) can cause multiple central nervous system (CNS) pathologies. Studies have found that indoleamine-2,3-dioxygenase (IDO, rate-limiting enzyme of the kynurenine (Kyn) pathway) deficient mice were protected from endotoxin induced cognitive impairment, and Kyn administration induced cognitive memory deficits in both control and IDO-deficient mice. However, there is no investigation of brain Kyn pathway in IBD, thus we investigated whether DSS-induced colitis could cause dysregulation of Kyn pathway in brain, and also in serum. We treated mice with 2% DSS for 10 consecutive days to induce colitis. In serum, we found significant increase in Kyn level and kynurenic acid (Kyna) level, which was regulated by IDO-1 and KAT2 (rate-limiting enzymes of Trp-Kyn-Kyna pathway). Similarly, we also found elevated IDO-1 levels in peripheral blood monocytes and colon of UC patients by analyzing GEO datasets. Furthermore, Kyn pathway was significantly upregulated in the cerebral cortex under the action of IDO-1 after DSS treatment, which ultimately induced neurotoxic phenotype of astrocyte. To investigate whether gut microbiota is involved in IBD-induced Kyn pathway dysregulation, we performed intestinal flora 16S rRNA sequencing and found that DSS-induced colitis significantly altered the composition and diversity of the gut microbiota. Metabolic function analysis also found that Tryptophan metabolism, NOD-like receptor signaling pathway and MAPK signaling pathway were significantly up-regulated in the 2% DSS group. Significant association between intestinal flora and Trp metabolism (both in serum and brain) was found by correlation analysis. Overall, our study revealed that DSS-induced colitis causes dysregulation of Kyn pathway in serum and brain by affecting rate-limiting enzymes and intestinal flora.